2008
DOI: 10.1091/mbc.e07-08-0753
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of c-Jun Reduces Cellular Migration and Invasion through Inhibition of c-Src and Hyperactivation of ROCK II Kinase

Abstract: The spread of metastatic tumors to different organs is associated with poor prognosis. The metastatic process requires migration and cellular invasion. The protooncogene c-jun encodes the founding member of the activator protein-1 family and is required for cellular proliferation and DNA synthesis in response to oncogenic signals and plays an essential role in chemical carcinogenesis. The role of c-Jun in cellular invasion remains to be defined. Genetic deletion of c-Jun in transgenic mice is embryonic lethal;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 51 publications
2
24
0
Order By: Relevance
“…For example, AP-1 can act synergistically with AP-4 to activate SV40 late gene transcription (41,42). A component of AP-1 the oncoprotein c-jun has been shown to be hyperactivated by JNK in epithelial cells (43). Our observations showing JNK involvement in the regulation of AP-4 activity following IGF-1 stimulation are supported by a study wherein AP-4 was shown to be downregulated by glucocorticoids (44).…”
Section: Discussionsupporting
confidence: 73%
“…For example, AP-1 can act synergistically with AP-4 to activate SV40 late gene transcription (41,42). A component of AP-1 the oncoprotein c-jun has been shown to be hyperactivated by JNK in epithelial cells (43). Our observations showing JNK involvement in the regulation of AP-4 activity following IGF-1 stimulation are supported by a study wherein AP-4 was shown to be downregulated by glucocorticoids (44).…”
Section: Discussionsupporting
confidence: 73%
“…Transgenic Mice, Expression Plasmids, and Promoter Cloning-Transgenic animals carrying floxed c-jun alleles, c-jun f/f , and the MMTV-ErbB2 transgenic mice were previously described (12,26,27). All experimental procedures performed using these mice were approved by the Institutional Animal Care and Use Committee (IACUC) of Thomas Jefferson University.…”
Section: Methodsmentioning
confidence: 99%
“…The retroviral expression plasmid encoding Cre was cloned through the insertion of the cDNA from the vector pMC-Cre-PGK-Hyg (from Dr. P. Stanley) as an EcoRI fragment into the retroviral expression plasmid pMSCV-IRES-GFP (30). Expression of Cre from pMSCV-IRES-GFP vector was confirmed by Western blot using an antibody directed to Cre (MMS-106) (12). The EcoRI fragment of the rat c-Jun DNA (31) was subcloned into the retroviral expression vector MSCV-IRES-GFP to form MSCV-c-Jun-IRES-GFP.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of c-Src transducer is elevated in the most aggressive breast carcinomas (29), and seems to regulate NF-κB activity, to increase HDAC3 phosphorylation and to affect HDAC3 nuclear translocation, which may also depend on a decrease in interaction with IκBα (30)(31)(32). c-Src overexpression, which is sometimes c-Jun dependent, may represent a system regulating cell migration (33). HDACs function as corepressors/coactivators of transcription factors by means of as yet unclear mechanisms, although HDAC3 is a corepressor of NF-κB through the deacetylation of p65 (34,35).…”
Section: Introductionmentioning
confidence: 99%